L’abbé Thomas Thobert (1736-1777), sa pastorale et son œuvre théâtrale - Régis Bertrand (Revue des Langues Romanes)
Thomas Thobert (Gémenos, 30 December 1736-Marseilles, 27 August 1777), a student and then a member of the priestly Society of the Sacred Heart (Sacré-Cœur) in Marseilles, left both a treatise on theology in Latin and theatrical pieces in Provençal, including a Christmas pastorale. These works were intended for an audience of educated adolescents and young men who were pursuing secondary studies with the priests of the Sacré-Cœur, for whom a good command of French was a social requirement and a knowledge of Latin was part of their training. The posthumous dissemination of his pastorale through print was initially performed by the last priests of the Sacré-Cœur, within their seminary and in the parish of Notre-Dame du Mont de Marseille, where the Society continued until the Second Empire. There are a total of around a dozen editions. The study of these booklets suggests that there had been two texts, probably intended for different audiences. They deal with the Annunciation to the Shepherds and the Adoration of the Shepherds before the manger. The shepherds speak Provençal, which accounts for a little more than half of the verse. The "Eternal Father" and the angels speak French, and the angels also sing in Latin. Antoine Maurel’s pastorale, first performed in 1842, was written for the charity in favour of young workers run by the church of Notre-Dame du Mont in Marseilles, and directly follows the format handed down by the priests of the Sacré-Cœur. But Maurel added a plot and socially distinctive characters, as are found in the scripts for the talking Nativity scenes (puppet theatre). His pastorale was soon adopted in place of the one by Father Thobert.